Role of antibiotic prophylaxis in antenatal hydronephrosis: A systematic review from the European Association of Urology/European Society for Paediatric Urology Guidelines Panel - Silay, Mesrur Selcuk; Undre, Shabnam; Nambiar, Arjun K; Dogan, Hasan Serkan; Kocvara, Radim; Nijman, Rien J M; Stein, Raimund; Tekgul, Serdar; Radmayr, Christian (Journal of pediatric urology, 2017)
BACKGROUND: The benefits and harms of continuous antibiotic prophylaxis (CAP) versus observation in patients with antenatal hydronephrosis (ANH) are controversial. OBJECTIVE: The aim was to determine the effectiveness of CAP for ANH, and if beneficial to determine the best type and regimen of antibiotic and the most harmful to provide guidance for clinical practice. METHODS: A systematic literature search was performed in databases including Medline, Embase, and Cochrane in June 2015. The protocol was prospectively registered to PROSPERO (CRD42015024775). The search started from 1980, when maternal ultrasound was first introduced into clinical practice. Eligible studies were critically evaluated for risk of bias using Revman software. The outcomes included reduction in urinary tract infections (UTI), drug-related adverse events and kidney functions. RESULTS: Of 797 articles identified, 57 full text articles and six abstracts were eligible for inclusion (2 randomized controlled trials, 11 non-randomized comparative studies, and 50 case series). It remains unclear whether CAP is superior to observation in decreasing UTIs. No conclusion could be drawn for drug-related adverse events and kidney function because of lack of data. Children who were not circumcised, with ureteral dilatation, and high-grade hydronephrosis may be more likely to develop UTI, and CAP may be warranted for these subgroups of patients. A majority of the studies had low-to-moderate quality of evidence and with high risk of bias. CONCLUSIONS: The benefits of CAP in a heterogeneous group of children with ANH involving different etiologies remains unproven. However, the evidence in the form of prospective and retrospective observational studies has shown that it reduces febrile UTI in particular subgroups.
Keywords: Urinary Tract Infections; novorozenec; hydronefróza; lidé; Hydronephrosis; infekce močového ústrojí; Antibiotic Prophylaxis; Humans; antibiotická profylaxe; Infant, Newborn